Investigation on the Tensile and Flexural Properties of Coir-fibre-reinforced Polypropylene Composites - Begum, K.; Islam, M. A.; Huque, M. M. (Journal of Scientific Research, 2015)
The utilization of natural fibres as reinforcement in polymer composites has been increased significantly for their lightweight, low cost, high specific strength, modulus and biodegradable characteristic. In this present work, the mechanical properties of randomly distributed short coir-fibre-reinforced polypropylene (PP) composites have been studied as a function of fibre loading. In order to improve the composites mechanical properties, raw coir fibres were treated with 1% alkali (NaOH) solution. Both raw and alkali treated coir-fibre-reinforced PP composites were prepared with different fibre loadings (10, 15, 20, 25, 30 and 35 wt%) using a double roller open mixer machine and injection molding machine. The mechanical properties, such as tensile strength (TS), tensile modulus (TM), flexural strength (FS) and flexural modulus (FM) were investigated for the prepared composites. The alkali treated coir-fibre-reinforced PP composites showed better results in mechanical properties compared to untreated composites. Finally, the optical microscopic studies were carried out on fractured surfaces of the tensile test specimens, which indicated weak interfacial bonding between the fibre and the polymer.